Acid-Base Resistant Zone in Teeth with the Direct Restoration Using Different Adhesive System Generations: A Systematic Review - Zurab Khabadze; Ekaterina Shilyaeva; Alexandra Kotelnikova; David Todua; Yusup Bakaev; Saida Abdulkerimova; Oleg Mordanov (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2023)
Objective: To find out what the acid-base resistant zone (ABRZ) is and the mechanism of its formation. Material and Methods: This systematic review was based on the search of laboratory studies in which self-etching adhesive systems were used. The electronic database PubMed was used for the search. The search began on August 2021 and ended on June 2022. We have analyzed the materials and methods of each research and entered them in the appropriate tables to give a clearer assessment of the obtained results. Results: This systematic review included 15 full-text articles published from 2011 to 2019. The ABRZ is formed on both dentine and enamel. On dentine, the ABRZ is formed only when using self-etching adhesive systems; on the enamel, on the contrary, the step of preliminary etch and rinse contributes to the formation of a thicker ABRZ. The functional monomer MDP and fluorine increase the thickness of the ABRZ and provide a hybrid layer /ABRZ boundary without defects and erosions. Conclusion: Self-etching adhesive systems ensure the creation of an ABRZ resistant to acid-base tests. This phenomenon can provide the resistance of tooth tissues to demineralization, and therefore increase their resistance to caries.